Pabrik Pakan Ternak - Adrianus Herman Jamlean; Muchlis Alahudin; Jeni Paresa (Faculty of Engineering, Musamus University, Merauke, Papua, Indonesia., 2020)
The term industry is often identified with all human economic activities that process raw goods or raw materials into semi-finished goods or finished goods. From this definition, the term industry is often referred to as manufacturing activities. The animal feed industry is an industry that carries out processing, testing of feeds and promotion of animal feed produced to farmers in increasing livestock production of higher quality. Data collection in research is very important to answer the problem in research. The method used is through written questions submitted to the informant (Head of the Livestock Service Office). In this case, the data collection methods that researchers use in this study, namely observation and interviews. Research interview is a research method which includes collecting data through direct question and answer interaction between interviewer (researcher) and respondent (informant) to gather as much information as possible on the problem under study.